2018
DOI: 10.1155/2018/5048031
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory and Antioxidant Properties of Black Mulberry (Morus nigra L.) in a Model of LPS‐Induced Sepsis

Abstract: Sepsis is a complex disease and is the cause of many deaths worldwide. Sepsis pathogenesis involves a dysregulated inflammatory response with consequent production of inflammatory mediators and reactive species. The production and excessive release of these substances into the systemic circulation trigger various cellular and metabolic alterations that are observed during the disease evolution. Thus, more studies have been carried out to investigate the therapeutic potential of plants such as Morus nigra L., p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…Nevertheless, the concentrations of TNF-α and IL-6 in the culture medium were dose-dependently reduced in the cells co-treated with HM at concentrations of 0.1, 0.5, and 1 μg/mL compared to the LPS control, as shown in Figure 5. Consistent with our results, in a model of lipopolysaccharide (LPS)-induced sepsis, black mulberry ( Morus nigra L.) presented anti-inflammatory properties by lowering the serum TNF-α levels [25]. In addition, the combination of mulberry fruit and leaf extracts improved inflammation by suppressing the TNF-α and NOS2 expression in adipose tissue and liver of obese mice [26,27].…”
Section: Resultssupporting
confidence: 73%
“…Nevertheless, the concentrations of TNF-α and IL-6 in the culture medium were dose-dependently reduced in the cells co-treated with HM at concentrations of 0.1, 0.5, and 1 μg/mL compared to the LPS control, as shown in Figure 5. Consistent with our results, in a model of lipopolysaccharide (LPS)-induced sepsis, black mulberry ( Morus nigra L.) presented anti-inflammatory properties by lowering the serum TNF-α levels [25]. In addition, the combination of mulberry fruit and leaf extracts improved inflammation by suppressing the TNF-α and NOS2 expression in adipose tissue and liver of obese mice [26,27].…”
Section: Resultssupporting
confidence: 73%
“…Acute colon injury mice model was built by intraperitoneal injection (i.p.) with 10 mg/kg LPS (Sigma, Shanghai, China) for 24 h as described before ( 29 31 ). BRD4 inhibition was applied by i.p.…”
Section: Methodsmentioning
confidence: 99%
“…A very recent study [ 21 ] has shown that extracts of M. nigra pulps and leaves can improve survival rate and decrease the number of total leukocytes in bronchoalveloar lavage fluid in LPS-induced septic mice, indicating the reduction of inflammatory infiltrate in the lung. Although most hepatic and serum cytokine levels were not changed by the administration of M. nigra extracts, serum levels of TNF, an important mediator of sepsis, were significantly lower in the M. nigra extract-treated group than those in the septic animal group.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%